2023
DOI: 10.3390/nu15183950
|View full text |Cite
|
Sign up to set email alerts
|

Moderate- and High-Intensity Endurance Training Alleviate Diabetes-Induced Cardiac Dysfunction in Rats

Sarah D’Haese,
Maxim Verboven,
Lize Evens
et al.

Abstract: Exercise training is an encouraging approach to treat cardiac dysfunction in type 2 diabetes (T2DM), but the impact of its intensity is not understood. We aim to investigate whether and, if so, how moderate-intensity training (MIT) and high-intensity interval training (HIIT) alleviate adverse cardiac remodeling and dysfunction in rats with T2DM. Male rats received standard chow (n = 10) or Western diet (WD) to induce T2DM. Hereafter, WD rats were subjected to a 12-week sedentary lifestyle (n = 8), running MIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 125 publications
(193 reference statements)
3
5
0
Order By: Relevance
“…In this model, the WD for 18 weeks led to weight gain, insulin resistance and disturbed glucose tolerance, as well as cardiac complications, including LV hypertrophy and increased EDP, while the EF remained preserved. When the WD regime was continued, the rats displayed hypertension, increased ESV and pronounced reduction in EF by 30 weeks [17]. Metabolically, we have now shown that both MIT and HIIT are able to prevent the development of insulin resistance and improved glucose tolerance in WD-fed rats, confirming results in clinical trials on patients at risk for T2DM, as has been reviewed elsewhere [29].…”
Section: Mit and Hiit As Cardioprotective Strategies In The Developme...supporting
confidence: 83%
See 4 more Smart Citations
“…In this model, the WD for 18 weeks led to weight gain, insulin resistance and disturbed glucose tolerance, as well as cardiac complications, including LV hypertrophy and increased EDP, while the EF remained preserved. When the WD regime was continued, the rats displayed hypertension, increased ESV and pronounced reduction in EF by 30 weeks [17]. Metabolically, we have now shown that both MIT and HIIT are able to prevent the development of insulin resistance and improved glucose tolerance in WD-fed rats, confirming results in clinical trials on patients at risk for T2DM, as has been reviewed elsewhere [29].…”
Section: Mit and Hiit As Cardioprotective Strategies In The Developme...supporting
confidence: 83%
“…In diabetic cardiomyopathy, excessive formation of LV interstitial fibrosis is one of the main disease hallmarks and underlies pathological concentric remodeling [3]. We and others have previously shown that MIT and HIIT have therapeutically decreased interstitial fibrosis content in the LV areas of diet-induced T2DM rats with cardiac dysfunction [17,38,42]. Here, we have validated these findings in preventive settings, as both exercise training modalities reduced LV interstitial fibrosis.…”
Section: Mechanisms Of Exercise-training-induced Cardioprotectionsupporting
confidence: 72%
See 3 more Smart Citations